Mapping Higher Order Thinking Skills in English for Specific Purposes Classes - Herreño-Contreras, Yomaira Angélica (2023)
This article displays the main foundations and findings of a research on Higher Order Thinking Skills (HOTS) in legal English courses at Universidad Santo Tomás in Villavicencio (Colombia), intended to provide an answer to the following question: What is the impact of fostering Higher Order Thinking Skills (HOTS) within legal English classes? The study was a descriptive longitudinal mixed methods approach research developed over two years with 56 law students with an age range between 21 and 23 years that delved into three issues, namely, students’ perceptions concerning legal English classes, after two years of participating in lessons designed under Bloom’s taxonomy; students’ insights regarding HOTS and their influence on learning a foreign language and on their future performance as lawyers, and the identification and analysis of strengths and weaknesses of the methodology implemented. The data collection instruments were a survey, a semi-structured interview, and the artifacts made by the students. The results suggest that students ponder on the relevance of HOTS in terms of the instruction received at the university and their future professional performance; however, they do not have a clear understanding of the features and actions correlated to analysis, evaluation, and creation. It is evident that greater exposure to learning experiences involving higher thinking is required, and its interconnection with daily life beyond the classroom.